Investigation of electrical conductivity, optical property, and stability of 2D MXene nanofluid containing ionic liquids - Bakthavatchalam, B. (MDPI AG, 2020)
The addition of ionic liquids with MXene nanofluid has a substantial impact on the solar thermal collectorsâ working fluidâs optical properties that effectively absorb and distribute solar radiation. Increased solar radiation absorption potential ensures that heats are transported more rapidly and effectively. This research endeavors to investigate the concept of accumulating solar energy via the usage of ionic liquid-based 2D MXene nanofluid (Ionanofluids) for solar applications. In this study, the optical potential of Diethylene Glycol/MXene nanofluid incorporated with 1-ethyl-3-methyl imidazolium octyl sulfate (EmimOSO4 ) ionic liquid was extensively investigated with respect to MXene concentration (0.1 to 0.4 wt%) and time (first day and seventh day) through UV-Vis Spectroscopy. A two-step approach was employed to synthesize the proposed ionanofluids with nanoparticle concentrations from 0.1 to 0.4 wt%. In wavelengths between 240 to 790 nm, the effect of ionic liquids, MXene concentration, and dispersion stability played a significant part in enhancing the absorbance capacity of the formulated MXene based Ionanofluid. Furthermore, the increase in the concentration of MXene nanoparticles resulted in more absorbance peaks facilitating high light absorption. Finally, the electrical conductivity of the ionanofluids is also analyzed as MXene renders them promising for solar cell applications. The utmost electrical conductivity of the formulated fluids of 571 ÂµS/cm (micro siemens per centimeter) was achieved at 0.4 wt% concentration. Â© 2020 by the authors. Licensee MDPI, Basel, Switzerland.